Synthesis of tetra(epoxy)-terminated open-cage POSS and its particle thermo-crosslinking with diphenols for fabricating high performance low-k composites adopted in electronic packaging. (5th January 2023) - Zhang, Zongwu; Zhou, Yijie; Yang, Yu; Ma, Xiaoyan; Xuan, Lixin; Wu, Xiao
Abstract: Polyhedral oligomeric silsesquioxanes (POSSs) are ideal particles to reduce the dielectric constant (k) and loss (tan δ ) values of resin matrixes for electronic packaging, but greatly limited by its finite addition due to phase-separation. Herein, tetra(epoxy)-terminated open-cage TG-POSS was synthesized and utilized as a unique building block to crosslink with bisphenol A or hexafluoro-bisphenol A, respectively, for the preparation of novel high performance low-k composites (POSS/BPA or POSS/FBPA). Results reveal that such rational design endows these two materials with homogeneous hybridization even at high POSS loading (>72.0 wt%), which is the main reason for superior dielectric, thermal and hydrophobic properties as compared with counterparts reported previously. Especially, fluorinated POSS/FBPA shows the lowest k value of 2.38, lowest tan δ value of 0.008, highest initial decomposition temperature of 396.1 °C and largest water contact angle of 117.0°, under the extra-contribution of trifluoromethyl units. In addition, its well-dispersed, moderate-crosslinked and rigid-flexible polymer network also leads to outstanding mechanical properties (elongation at break of 3.50% and modulus of 2.75 GPa) for practical applications. Summarily, this work highlights a useful strategy to fabricate high performance low-k composites with high POSS content, which is not only potential for advanced microelectronic industry but also instructive for academic fields. Graphical abstract: Image 1 Highlights: A tetra(epoxy) TG-POSS with inorganic open-cage structure was synthesized. TG-POSS was utilized to thermo-crosslink with diphenols for novel low-k composites. The prepared composites show advanced low-dielectric and other comprehensive properties. The superior properties are mainly attributed to the open-cages from TG-POSS. The prepared composites have broad application prospects for electronic packaging.